2018
DOI: 10.1002/jmv.25037
|View full text |Cite
|
Sign up to set email alerts
|

RSV‐hRV co‐infection is a risk factor for recurrent bronchial obstruction and early sensitization 3 years after bronchiolitis

Abstract: To assess risk factors of recurrent bronchial obstruction and allergic sensitization 3 years after an episode of acute bronchiolitis, whether after ambulatory care treatment or hospitalization. A monocentric prospective longitudinal study including infants aged under 1 year with acute bronchiolitis was performed, with clinical (severity score), biological (serum Krebs von den Lungen 6 antigen), and viral (14 virus by naso-pharyngeal suction detection) assessments. Follow-up included a quaterly telephone interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Our own results show a 4-fold increased risk of asthma in children with allergic sensitization. Therefore, although Amat et al, (27) did not nd association between viral coinfection and asthma at 3 years, the association of coinfections with allergic sensitization could be a predictor of asthma development in these coinfected children later in life.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our own results show a 4-fold increased risk of asthma in children with allergic sensitization. Therefore, although Amat et al, (27) did not nd association between viral coinfection and asthma at 3 years, the association of coinfections with allergic sensitization could be a predictor of asthma development in these coinfected children later in life.…”
Section: Discussionmentioning
confidence: 80%
“…Amat et al, (27), in a 3-year follow-up study of 154 children with a previous history of bronchiolitis (inpatient and outpatient), observed that 46.8% of them had been diagnosed with recurrent wheezing at age 3, identifying as risk factors only a family background of atopy and living in an apartment. In contrast, neither the type of virus identi ed, nor the single or multiple viral infections showed association with recurrent wheezing development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they confirmed the lack of association between RSV bronchiolitis and wheezing [ 46 ]. On the contrary, the study of Amat and colleagues [ 47 ] on a cohort of 154 hospitalized infants for bronchiolitis did not find any difference between the kind of respiratory virus (RSV in 76% of cases, RV in 28.6%, other viruses in 70.1% of cases) and the subsequent development of recurrent bronchial obstruction (intended as ≥3 respiratory symptoms documented in ≥2 times). However, the same study demonstrated that RV + RSV co-infected bronchiolitis was associated with the risk of sensitization to aeroallergens at three years at the multivariate analysis ( p = 0.02) [ 47 ].…”
Section: Long-term Sequelae Of Rv Bronchiolitismentioning
confidence: 91%
“…RV bronchiolitis has been found statistically associated with eosinophilia, especially with a blood eosinophil count >400/mm 3 [ 34 , 46 ], more frequently than non-RV bronchiolitis [ 19 , 28 , 30 ]. Moreover, as mentioned earlier, Amat and colleagues in 2018 found a correlation between co-infected RV + RSV bronchiolitis and the increased risk of sensitization to aeroallergens at three years at multivariate analysis [ 47 ]. The other peculiar RV-related immunological aspects are represented by the low IFN responses, especially IFN-γ.…”
Section: Long-term Sequelae Of Rv Bronchiolitismentioning
confidence: 97%
“…Sólo el 28% de los niños presentan antecedentes familiares de bronquiolitis/bronquitis, estos datos no muestran que esta variable sea factor de riesgo y vemos la limitación en nuestro trabajo de no haber añadido a ella otros factores como atopia familiar, asma familiar, descritos en otros estudios como factores de riesgo (90)(91)(92).…”
Section: Discussionunclassified